2021
DOI: 10.1007/s40262-021-01038-6
|View full text |Cite
|
Sign up to set email alerts
|

Etomidate and its Analogs: A Review of Pharmacokinetics and Pharmacodynamics

Abstract: Etomidate is a hypnotic agent that is used for the induction of anesthesia. It produces its effect by acting as a positive allosteric modulator on the γ-aminobutyric acid type A receptor and thus enhancing the effect of the inhibitory neurotransmitter γ-aminobutyric acid. Etomidate stands out among other anesthetic agents by having a remarkably stable cardiorespiratory profile, producing no cardiovascular or respiratory depression. However, etomidate suppresses the adrenocortical axis by the inhibition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 156 publications
(234 reference statements)
0
55
0
Order By: Relevance
“…Recent studies have shown no correlation between involuntary muscle movement and epilepsy (Valk et al, 2019), although, disinhibitory effects of the Bispectral Index (BIS) are associated with involuntary muscle movements . The mechanisms underlying clinical excitation are still unclear, and ABP-700 was restarted in 2020 with funding by Mass General Brigham (Boston, MA, United States), which still needs further investigation (Valk and Struys, 2021).…”
Section: Sedatives Etomidate and Analoguesmentioning
confidence: 99%
“…Recent studies have shown no correlation between involuntary muscle movement and epilepsy (Valk et al, 2019), although, disinhibitory effects of the Bispectral Index (BIS) are associated with involuntary muscle movements . The mechanisms underlying clinical excitation are still unclear, and ABP-700 was restarted in 2020 with funding by Mass General Brigham (Boston, MA, United States), which still needs further investigation (Valk and Struys, 2021).…”
Section: Sedatives Etomidate and Analoguesmentioning
confidence: 99%
“…This was shown to be caused by etomidate-induced inhibition of the 11β-hydroxylase enzyme causing adrenocortical suppression [ 48 ]. Since then, the use of etomidate has been limited to the induction of general anaesthesia in select patient groups, in whom the proposed haemodynamic stability after etomidate induction outweighs the risk of adrenal suppression [ 3 ]. Since the late 2000s, analogues of etomidate have been in development with the aim to eliminate the adrenocortical suppressive action while retaining its haemodynamically stable profile.…”
Section: New Hypnotic Agentsmentioning
confidence: 99%
“…Etomidate mainly acts on the α and β subunits of GABAA ( Forman, 2011 ). Besides, Etomidate inhibits the adrenal cortical axis by inhibiting the enzyme 11β-hydroxylase and mainly is metabolized by hepatic esterase ( Valk and Struys, 2021 ). Etomidate metabolism in animals and humans depends on hepatic esterase activity, which hydrolyzes it to a carboxylic acid and an ethanol leaving group ( Forman, 2011 ).…”
Section: Introductionmentioning
confidence: 99%